Scholarship of Syekh Jamaluddin Al-Qasimi (1282 H-1332 H) In Education - MHD Harmidi HRP; Tengku Sarina Aini Tengku Kasim; Ahmad Yussuf (al-Afkar, Journal For Islamic Studies, 2024)
Education is an important thing in Islam. Every Muslim is encouraged to seek various types of knowledge. The importance of this education is clearly stated in the Qur’an and Sunnah and explained by Islamic scholars in their great works.This paper reveals the involvement and commitment of Sheikh Jamaluddin al-Qasimi in the field of education. He was a great contemporary scholar in Syria who produced several works discussing educational ideas. This paper focuses on his involvement in the field of education which includes an analysis of his students and his students and his educational works. This debate further examines his contributions and works in the field of education. The results of the study found that al-Qasimi has contributed a lot in the field of moral education, morality to oneself, morality to Allah SWT and his massanger, morality in the home and social society.